The Impact of Green Economy Implementation on Financial Performance and Sustainability of MSME Business Models in Indonesia - Audina, Mia (International Journal of Business, Law, and Education, 2026)
This study aims to analyze the influence of green economy implementation on the financial performance and sustainability of MSME business models in Indonesia. Employing a quantitative approach and Structural Equation Modeling–Partial Least Squares (SEM-PLS) analysis, this research examines MSMEs that have adopted environmentally sustainable practices through green innovation, green accounting, and green human resource management. The findings indicate that implementing the green economy has a positive, statistically significant effect on financial performance, with financial performance serving as a partial mediator, reinforcing the relationship between green practices and the sustainability of business models. These results substantiate the notion that successful green transformation not only engenders environmental legitimacy but also enhances financial resilience, which serves as the foundation for MSMEs' long-term competitiveness. Practically, this research offers implications for policymakers to strengthen the green regulatory and financing ecosystem, for MSME stakeholders to incorporate innovation alongside financial literacy and digitalization, and for financial institutions to develop inclusive, environment-based funding instruments.